Understanding Landscape Aesthetics Using a Novel Viewshed Assessment of Social Media Locations Within the Troodos UNESCO Global Geopark, Cyprus - Fox, Nathan; Chamberlain, Brent; Lindquist, Mark; Van Berkel, Derek (Frontiers in Environmental Science, 2022)
Globally, geodiversity and the associated ecosystem services it provides, are both under threat from anthropogenic pressures and environmental changes. The UNESCO Global Geoparks Programme was established to create protected areas that not only preserve geodiversity but enhance human wellbeing and cultural heritage. Understanding the role geodiversity plays in providing such ecosystem services is necessary for providing holistic conservation priorities that ensure their sustainable use. Studies have extensively used social media data to assess cultural ecosystem services, however, the photographic viewable area, which demonstrates scenic or areas of interest, has been scarcely evaluated. Studies often take crude measurements of viewsheds rather than isolating viewed content. Here, we gather georeferenced images taken inside geopark boundaries from the social media website Flickr as a proxy for aesthetically pleasing viewpoints. To understand what landscape characteristics are visible from these viewpoints we calculate viewshed analysis following the novel visual magnitude approach. The use of magnitude viewshed provides a metric for visual relevancy compared to traditional viewshed approaches that only provide a binary metric representing visible or non-visible. Here, we find that the use of the visual magnitude methodology provides richer information about what is visible than from traditional viewshed analysis. We find that aesthetically appreciated views as inferred by social media within the Troodos Geopark, Cyprus, do not only include natural features such as forest and water but are often related to geodiversity and anthropogenically altered landscapes such as mineral extraction sites and vineyards, for which the geopark is known. These results can help to inform geoconservation practices with the goal of sustainable access and enjoyment of aesthetic services.